2021
DOI: 10.1039/d0cy02161j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient non-noble Ni–Cu based catalysts for the valorization of palmitic acid through a decarboxylation reaction

Abstract: The synergistic effect Ni–Cu in the bimetallic catalyst Ni–Cu/C improved the stability and reduction temperature as well as enhanced the catalytic activity for the decarboxylation of palmitic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…In addition, the newly added metal may affect the reduction state of another metal, resulting in completely different active components of the catalyst [49,80,81,89,96,97,101] . For example, Kim and co‐workers found that when Pd was added to Cu, the H 2 consumption peaks of Cu shifted to lower reduction temperature, which revealed that the synergistic interaction between Cu and Pd enhanced the reducibility of the Cu species [49] .…”
Section: Bimetallic Catalyst Supported On Carbonmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the newly added metal may affect the reduction state of another metal, resulting in completely different active components of the catalyst [49,80,81,89,96,97,101] . For example, Kim and co‐workers found that when Pd was added to Cu, the H 2 consumption peaks of Cu shifted to lower reduction temperature, which revealed that the synergistic interaction between Cu and Pd enhanced the reducibility of the Cu species [49] .…”
Section: Bimetallic Catalyst Supported On Carbonmentioning
confidence: 99%
“…The charge transfer of bimetallic catalysts will affect the electron density of metal surface, forming an electron deficient state of one metal and an electron rich state of another metal, thus affecting the adsorption and subsequent activation of substrate molecules [82,87,91,96,97,106] …”
Section: Bimetallic Catalyst Supported On Carbonmentioning
confidence: 99%
See 3 more Smart Citations